Lithuanian identity: Between the historical experience of central and eastern Europe and the heritage of the great duchy of Lithuania - Berenis, Vytautas (Creativity Studies, 2008)
This article deals with the influence of the heritage of the Great Duchy of Lithuania (GDL) on the contemporary development of Lithuanian identity, emphasizing the reasons of its actualization. The actualizing of the GDL is closely connected with the processes of globalization, euro‐integration and geopolitical alternations. The author affirms that the historical heritage of the GDL helps Lithuania, Poland, Belarus and Ukraine to integrate into the space of Eastern Europe and the supposed national tolerance in the GDL is peculiar manifestation of the democratic tradition in this area.Lietuvių tapatumas: tarp vidurio ir rytų Europos istorinės patirties bei Lietuvos didžiosios kunigaikštystės paveldoSantrauka. Nagrinėjama Lietuvos Didžiosios Kunigaikštystės (LDK) paveldo įtaka dabartinei lietuvių tapatumo raidai, akcentuojamos jo aktualumo priežastys. Šiuolaikinėje epochoje LDK aktualumas susijęs su globalizacijos, eurointegracijos procesais, geopolitiniais pokyčiais. Teigiama, kad LDK istorinis paveldas padeda Lietuvai, Lenkijai, Baltarusijai ir Ukrainai integruotis į Rytų Europos erdvę, o tariamoji tautinė tolerancija LDK valstybėje yra savotiška demokratinės tradicijos šiame areale apraiška.Reikšminiai žodžiai: geopolitika, Lietuvos Didžiosios Kunigaikštystės istorija ir kultūra, Lietuvos kultūros istorija, nacionalinis tapatumas.First Published Online: 14 Oct 2010